A tri-modal paper device based on flower-like CuSe for the detection of an Alzheimer's disease-associated microRNA marker. Issue 23 (1st March 2022) - Zhu, Yaqi; Tian, Yang; Zheng, Tingting
Abstract : A tri-modal paper device based on flower-like CuSe was developed for monitoring Alzheimer's disease-related miRNA by integrating colorimetric, photothermal and surface-enhanced Raman scattering approaches. Abstract : A tri-modal paper device based on flower-like CuSe was developed for monitoring Alzheimer's disease (AD)-related miRNA by integrating colorimetric, photothermal and surface-enhanced Raman scattering approaches. Significantly, false-negative signals at the early stage of AD were completely eliminated by using our presented tri-modal strategy.